Rola tłumacza pisemnych tekstów specjalistycznych na podstawie własnych doświadczeń traduktologicznych - Bobowska-Nastarzewska, Patrycja (Investigationes Linguisticae, 2019)
The goal of this paper is to determine a translator’s role in the process of translation of a scientific text. The analysis centres on philosophical texts translated from French into Polish by the author of the paper: Plotinus or the Simplicity of Vision by Pierre Hadot, Philosophizing ad Infinitum by Marcel Conche, Intellectual Autobiography by Paul Ricœur, Speech and Action in Heraclitus. On the Theoretical Foundations of Moral Action by Michel Fattal, and Le Logos dans le Sophiste de Platon by Michel Fattal. A requirement is usually imposed on the translator of a specialist text to be invisible, transparent, and neutral. However, this analysis shows that this requirement cannot be met in translations of scientific texts.